Efficacy and cost-effectiveness of an online mindfulness program (MindOnLine) to reduce fear of recurrence among people with cancer: study protocol for a randomised controlled trial. Issue 1 (12th January 2022) - Livingston, Patricia M; Russell, Lahiru; Orellana, Liliana; Winter, Natalie; Jefford, Michael; Girgis, Afaf; Austin, David; O, Eric; Mihalopoulos, Cathrine; Ugalde, Anna; Chambers, Richard; Phipps-Nelson, Jo; et al.
Abstract : Introduction: Fear of cancer recurrence (FCR) is a common condition among cancer survivors that can lead to significant levels of distress, anxiety and depression. Online mindfulness programmes may provide the mechanism to support cancer survivors manage FCR and distress, and improve people's well-being over the short, medium and long term. The primary aim of this study is to determine the potential efficacy of MindOnLine, a 9 session mindfulness-based programme for survivors of breast, prostate and colorectal cancer. A formal economic programme will also be conducted. Methods and analysis: A single-blind randomised controlled trial to determine the efficacy and cost-efficacy of a MindOnLine programme for cancer survivors. A total of 400 people living with cancer will be recruited via online advertisements on social media platforms, peak consumer advocacy groups or through outpatient services at healthcare providers across Victoria, Australia. People will be randomly allocated to either the MindOnLine programme (n=200) or waitlist control (n=200). Participant assessments will occur at baseline, at 9 weeks and 9-month follow-up. The primary outcome is change in Fear of Recurrence Index Score total score between baseline and 9 weeks; secondary outcomes are changes in depression and anxiety, quality of life and mindfulness. The economic analysis comprises a cost-consequences analysis where all outcomes will be compared with costs. Ethics and dissemination: Ethics approval was obtained from the Peter MacCallum Cancer Centre (20-53) and Deakin University (2020-284). All participants will be required to provide written informed consent. Findings will be disseminated in peer reviewed journals and among key stakeholder organisations including hospitals, cancer and community organisations and Government. If successful the project will be rolled out nationally with a formal implementation plan. Trial registration number: Australian New Zealand Clinical Trials Registry (12620000645954); Pre-results. Registered 6 June 2020, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=379520&isReview=true .